2017
DOI: 10.3329/jbsp.v12i1.33921
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Thiamine in Male Long Evans Rats

Abstract: Background: The concept of analgesic effects of thiamine along with other B vitamins has been supported since long by various clinical and experimental evidences, though effects of individual thiamine on pain are yet to be clearly demonstrated. Objective: To assess the effects of increasing doses of thiamine supplementation on pain. Methods: Forty-eight (48) male Long Evans rats (200±20 gm) were given thiamine (100, 200, 250, mg/kg/day; experimental) or normal saline (5 ml/kg/day; control) intraperitonealy (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…After surgery, the rats were placed into the individual cages with heating pad. Previous protocols ( 35 37 ) were adapted to this study involving postoperative administration of thiamine, which is known for analgesic and anti-inflammatory effects ( 30 33 ). Within the first 3 days after the operation, antibiotic (gentamicin, 40 mg/kg) was injected subcutaneously (s.q.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After surgery, the rats were placed into the individual cages with heating pad. Previous protocols ( 35 37 ) were adapted to this study involving postoperative administration of thiamine, which is known for analgesic and anti-inflammatory effects ( 30 33 ). Within the first 3 days after the operation, antibiotic (gentamicin, 40 mg/kg) was injected subcutaneously (s.q.)…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, inflammation, oxidative stress, autophagy, and endoplasmic reticulum stress leading to neurodegeneration, are known to be induced by thiamine deficiency ( 24 27 ), and we have recently reported that a high dose of thiamine results in a long-term optimization of the amino acid metabolism ( 28 ), potentially contributing to beneficial influence of thiamine on brain pathologies ( 29 ). It is also known that thiamine exerts analgesic and anti-inflammatory effects in different rat models including nerve injuries ( 30 33 ). The aim of this work is to estimate long-term changes in the NO • -related compounds in the cerebral cortex after SCI, and their potential normalization by thiamine treatment.…”
Section: Introductionmentioning
confidence: 99%